Subjective well-being indices in assessing happiness in Russia - Lyudmila S. Skachkova; Olga Ya. Gerasimova; Darya D. Krivosheeva-Medyantseva (Управленец)
Due to the multidimensionality and dynamism of today’s social life, there emerges the need to modify the principles of measuring the effectiveness of socio-economic policy. The article empirically tests and analyzes subjective metrics focused on “failures” in the socio-economic development which are impossible to identify through objective indicators only. These metrics are the subjective well-being indices for the Russian population in terms of gender and age, residence (by federal districts), level of education, marital status, presence of children, subjective health assessments, job and pay satisfaction. The methodological framework resides in Edward Diener’s subjective well-being theory. The method of index numbers and methods of descriptive statistics, including the multivariate frequency distribution of two attributes, are applied. The evidence base is comprised of panel data of The Russia Longitudinal Monitoring Survey – Higher School of Economics (RLMS-HSE) for 2013–2022. According to the research results, the minimum and maximum values of the life satisfaction index were observed in 2016 and 2022, respectively. The affective index of happiness was found to reach higher values compared to the cognitive assessment of it. The findings show that gender, age, region of residence, level of education, as well as satisfaction with health, job, wage and financial status affect the values and dynamics of happiness indices in Russia. A well-being measurement approach covering both objective and sub jective assessments of people’s life and its individual aspects allows identifying gaps in the system of socio-economic support for the population.